Waiting To Give - Ashley Craig; Ellen Garbarino; Stephanie A. Heger; Robert Slonim (Institute for the Study of Labor (IZA), 2014)
We estimate the effect of an increase in time cost on the return behavior of blood donors. Using data from the Australia Red Cross Blood Service, we ask what happens when pro-social behavior becomes more costly. Exploiting a natural variation in which donor wait times are random, we use the length of time a donor spends waiting to make his donation as our measure of cost. Our data allows us to go beyond measures of satisfaction and intention and estimate the effect of wait time on return behavior. We estimate that a 38% increase (20 minutes or one standard deviation) in the average wait would result in a 14% decrease in donations per year. Our results thus indicate that waiting is not merely frustrating, but has significant negative long-term social costs. Further, relying only on satisfaction and intention data masks not only the magnitude of the effects but also heterogeneous responses to increased wait time: the return behavior of males is more elastic than females and donors display diminishing sensitivity in the domain of losses. Finally, we discuss the implications of our findings for organizations that operate with a large and diffuse volunteer donor base.
Keywords: D04; D12; D61; D64; I18; 330; pro-social behavior; time cost; blood donation